Methods and research progress in the construction of animal models of osteosarcopenia: a scoping review - Weiwei,; Wang, Shixuan; Hou, Decai; Zhan, Libin (Frontiers in Endocrinology, 2023)
Osteosarcopenia(OS) is a significant health concern resulting from the ageing process. Currently, as the population grows older, the prevalence of OS, a disease that entails the synchronous degeneration of muscles and bones, is mounting. This poses a serious threat to the health of the elderly while placing an enormous burden on social care. In order to comprehend the pathological mechanism of OS and develop clinical drugs, it is pertinent to construct an efficient animal model of OS. To investigate the modelling techniques of diverse experimental models of OS and elucidate their respective benefits and drawbacks, with the purpose of furnishing a theoretical foundation to advance experimental research on OS.We searched PubMed, Embase database, China Knowledge Network, Wanfang data platform and Vipshop journal platform databases from 2000 through to September 1, 2023. We included animal studies on sarcopenia or osteoporosis or osteosarcopenia or sarcopenia-osteoporosis, modelling methods for osteosarcopenia. Two independently screened study abstracts and full reports and complete data extraction.Eventually, Of 112,106 citations screened. 4938 underwent full-text review and 38 met the inclusion criteria. we reviewed and analyzed the literature and categorized the animal models of OS into the following five categories: Aging OS models; Hormonal deficiency model of OS;Chemical injection to induce OS;Disuse OS models and Genetic engineering OS models.This review outlines animal modelling approaches for OS, providing a comprehensive summary of their advantages and disadvantages. The different models were evaluated and selected based on their respective strengths and weaknesses to enable higher quality research outcomes in various research directions. The most widely used and established approach is considered to be the ageing and chemical injection OS model, which has the advantages of excellent reproducibility and low cost.To gain a profound comprehension of the pathological mechanism of OS and to devise efficacious clinical treatments, it is imperative to establish a viable laboratory animal model of OS. This article surveys various modelling techniques assessing their benefits, drawbacks and areas of applicability while predominantly employing mice as the primary model animal. Additionally, the evaluation indicators of OS models are briefly described.